Constructions of legitimate force. The case of CS sprays - Rappert, Brian (The British journal of criminology, 2002)
The use of force by the police is an area of significant concern both within and outside the police. The police struggle to find effective but publicly acceptable options. Recently in the United Kingdom, the deployment of CS chemical incapacitant sprays has emerged as a key initiative in the protection of officers and the enforcement of the law. Yet, the sprays have proved controversial. Reflecting debates within criminology about the contribution of police tactics and equipment to public disorder, radically different assessments of the sprays have been offered. This paper examines the conditions under which assessments of the legitimacy of the CS sprays are made. The findings of this paper suggest the need to reframe existing analysis of the use of force